THE INFLUENCE OF USING FISH FERMENTED BY LACTIC ACID BACTERIA AS FEED SUBSTITUTION ON SERUM LIPID PROFILE OF BROILERS - Sumarsih, S.; Yudiarti, T.; Utama, C.S.; Rahayu, E.S.; Harmayani, E. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The study was aimed to examine the effect of the use of fish fermented by lactic acid bacteria(LAB) as a subtitution for fish meal on serum lipid profile of broiler. One hundred and twenty five dayoldbroiler chicks of CP 707 strains were divided into five groups for five treatments. A CompletelyRandomized Design was used in this experiment. The treatments were 0 (control), 2, 4, 6 and 8% fishfermented by LAB substitution of basal diet containing 8% fish meal. The parameters were blood lipidprofile including total cholesterol, Low Density Lipoprotein (LDL) and High Density Lipoprotein(HDL) cholesterol and triglycerides. Data was analyzed by one-way Analysis of Variance (ANOVA).When the F test indicated a significant effect, the differences between the mean values were analyzed byDuncan’s Multiple Range test. Results showed that using fish silage fermented by LAB on broiler’s feeddid not affect total cholesterol and HDL cholesterol, but significantly affect (p<0.05) levels of LDLcholesterol and serum triglycerides of broilers. Based on serum lipid profile, it could be concluded thatfish fermented by LAB can be used as a substitute for the 100% fish meal in broiler’s feed.